Quality of Life Using Music Therapy Elements for People with Intellectual Disabilities - Moceviciene, Aldona; Prudņikova, Ilga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Quality of life include all aspects of the way we live our lives. They allow us to fulfil our needs and aspirations. On the basis of results of the research possibile to make a confirmation that music, sociocultural activities using music therapy elements for  people with intellectual  disabilitiess influented expanding possibilities self-expression, activating self-action, stimulating self-conception. Said elements of socialization  impowering those people self – realizing through cultural — artistic activities, sociocultural projects. That one componded efective „normal“ and intellectually disabled  citizens communication and cooperation. Thus possible life quality optimization for people with mental deseases in abilities limited space.